VIBRATION NOISE AND OPTIMIZATION ANALYSIS OF FAN IMPELLER IN RANGE HOOD - ZHENG DaWei; LI Bin; CHEN ZhenLei; WENG JianSong; SHANG Qing (Jixie qiangdu)
Up to 81. 5 d B high noise occurs in the range hood fitted with original process impeller. This paper presents a method of combing experiment and numerical simulation to reduce the noise level of the range hood under the maximum working condition.First,noise and vibration test of range hood and excitation resource are conducted on a range hood fitted with impellers made by original approach and new process,respectively. Then,the differences between the processing technologies in making the two impellers are analyzed. Modal analysis of the above impellers are performed to determine the cause of the vibration noise. Results show that the thermal stress is generated in the production process,which changes the natural frequency of the impeller made by the original process.Moreover,the changed natural frequency is close to the excitation frequency,which leads to the severe vibration noise. However,less thermal stress is produced in the production process of the new impeller by adding one more step in the production. The final modified procedure is to increase the natural frequency of the impeller by thickening the impeller rear lap and use the original production process. Thus the problems caused by severe vibration noise of the impeller gets solved successfully.